Se préparer au pire: la défense civile et l’insécurité au Nouveau-Brunswick durant la Seconde Guerre mondiale - Labbé, Pierrick (Acadiensis, 2016)
This paper analyses the reasons behind the organization of the New Brunswick Civilian Volunteer Corps, a civil defence organization established during the Second World War. Driven by insecurity and the leadership of the provincial government, thousands of New Brunswickers took charge of the protection of their home. The intra-provincial initiative was based on a different concept of civil defence than what was promoted by the federal government, less strategic and more focused on estate preservation. The CVC was the expression of patriotism, insecurity and fear channeled into a form of citizen participation in the war.